Market Response to the Opening of GIIAS 2025: Empirical Evidence from Electric Vehicle-Related Stocks on the Indonesia Stock Exchange (ISE) - Dina Rahmawati; Veronika Santi Paramita (Yayasan Sinergi Kawula Muda, 2026)
The automotive industry is shifting toward electric vehicles, supported by Indonesian government policies and incentives. The opening of GIIAS 2025, which showcases electric vehicle innovations, may influence investor reactions in the Indonesia Stock Exchange. However, studies examining the impact of large-scale auto exhibitions such as GIIAS 2025 on abnormal returns and trading volume are still limited. Therefore, this study aims to fill this gap by analyzing how the capital market responds to the opening of GIIAS 2025, emphasizing its role as a multi-information event that may provide incremental insights beyond conventional event-study settings. This study employs a quantitative approach using the event study method to examine five automotive companies engaged in electric vehicle development. The observation period spans 10 days before the event, the event day, and 10 days after the event. The analysis applies descriptive statistics, normality tests, and one-sample t-tests to evaluate abnormal returns, while paired sample t-tests used to compare average abnormal returns and trading volume before and after the event. The findings indicate that only a few days surrounding the GIIAS 2025 opening show statistically significant abnormal returns. However, there are no significant differences in average abnormal returns trading volume when comparing the pre- and post-event periods overall. These results suggest that the information conveyed during the GIIAS 2025 opening did not generate a strong market reaction, supporting the semi-strong form of the efficient market hypothesis, which posits that markets quickly incorporate publicly available information into stock prices, even if the overall impact is not substantial.